Secondary Neoplasm Arising in Nevus Sebaceus of Jadassohn: A Case Report Emphasizing Early Recognition and Evaluation - Agung Bima Putera; Ennesta Asri; Indah Indria Sari (CV. AKBAR PUTRA MANDIRI, 2026)
Background: Nevus sebaceus of Jadassohn (NSJ) is a congenital hamartomatous lesion involving epidermal, sebaceous, and adnexal structures. The lesion typically appears at birth or early childhood and remains stable for years. Secondary neoplastic transformations, either benign or malignant, may occur during adolescence or adulthood. Case: A 15-year-old girl presented with a yellowish plaque on the vertex of her scalp, first noticed at the age of five. Over time, the lesion enlarged, and a bluish-gray nodule developed two weeks prior to presentation, accompanied by localized pain. Dermatological examination revealed a cerebriform yellow-orange plaque with bluish nodules and alopecia. Dermoscopy showed yellow globules, a homogeneous yellow-orange background, and blue-gray ovoid nests. Histopathology confirmed features consistent with NSJ, including epidermal hyperplasia, papillomatosis, sebaceous glands opening into the epidermis, immature hair follicles, and ectopic apocrine glands. In addition, basaloid cell proliferation with peripheral palisading and melanin pigment suggested a secondary neoplasm. The overall findings are consistent with pigmented trichoblastoma, although the possibility of a pigmented basal cell carcinoma cannot be definitively ruled out. Discussion: The findings indicate neoplastic transformation arising within NSJ. Secondary tumors may develop even in adolescence, making early recognition crucial. Clinical changes such as rapid growth, color change, or pain should raise suspicion and prompt histopathological confirmation. Identifying secondary neoplasms influences management decisions, including the need for surgical excision.Conclusion: This case highlights the need for early recognition and thorough evaluation of NSJ lesions, particularly in adolescence, to detect and manage secondary neoplastic changes effectively.